-
If x3 + 3 = 4( a3 + b3 ) and 3x + 1 = 4( a3 + b3 ) , then ( a2 - b2 ) is equal to x x3
-
- 4
- 0
- 1
- 2
- 4
Correct Option: C
x3 + | = 4( a3 + b3 ) | |
x |
3x + | = 4( a3 - b3 ) | |
x3 |
On adding,
x3 + 3x + | + | = 8a3 | ||
x | x3 |
⇒ | ![]() | x + | ![]() | 3 | = (2a)3 | |
x |
⇒ x + | = 2a | |
x |
⇒ a = | ![]() | x + | ![]() | |||
2 | x |
Similarly,
x3 + | - 3x - | = 8b3 | ||
x | x3 |
⇒ | ![]() | x - | ![]() | 3 | = (2b)3 | |
x |
⇒ x - | = 2b | |
x |
⇒ b = | ![]() | x - | ![]() | |||
2 | x |
∴ a2 - b2 = | ![]() | ![]() | x + | ![]() | 2 | - | ![]() | x - | ![]() | 2 | ![]() | |||
4 | x | x |
a2 - b2 = | × 4 = 1 | |
4 |